A Solution for Sustainable Utilization of Aquaculture Waste: A Comprehensive Review of Biofloc Technology and Aquamimicry - Nisar, Ubair; Peng, Daomin; Mu, Yongtong; Sun, Yu (Frontiers in Nutrition, 2022)
Biofloc technology (BFT) is gaining traction as a strategic aquaculture tool for boosting feed conversions, biosecurity, and wastewater recycling. The significant aspect of BFT is aquaculture with highest stocking density and minimal water exchange. It not only improves the water quality of a system by removing inorganic nitrogen from wastewater but also serves as a suitable feed supplement and probiotic source for cultured species. This technology is commonly used for shrimp and tilapia culture and can be used for both semi-intensive and intensive culture systems. Biofloc, when combined with formulated diets, forms a balanced food chain that improves growth performance. Nutrients in this system are continuously recycled and reused and form an efficient alternative system in aquaculture. In addition to the reduction in water exchange, it is also considered as a bio-security measure, since it prevents entry of disease from outside sources. Aquamimicry is an innovative concept that simulates natural estuarine conditions by developing copepods that act as supplementary nutrition especially for shrimp culture. The review highlights the process, significance, and development of BFT, its microbial interactions, nutritional value, transition from biofloc to copefloc, and concept of aquamimicry to sustainably improve aquaculture production.